National Surgical Adjuvant Breast and Bowel Project Study of Tamoxifen and Raloxifene trial: Advancing the science of recruitment and breast cancer risk assessment in minority communities. (April 2013) - McCaskill-Stevens, Worta; Wilson, John W; Cook, Elise D; Edwards, Cora L; Gibson, Regina V; McElwain, Diane L; Figueroa-Moseley, Colmar D; Paskett, Electra D; Roberson, Noma L; Wickerham, D Lawrence; Wolmark, Norman
Background: One of the first chemoprevention trials conducted in the western hemisphere, the National Surgical Adjuvant Breast and Bowel Project's (NSABP) Breast Cancer Prevention Trial (BCPT), demonstrated the need to evaluate all aspects of recruitment in real time and to implement strategies to enroll racial and ethnic minority women. Purpose: The purpose of this report is to review various patient recruitment efforts the NSABP developed to enhance the participation of racial and ethnic minority women in the Study of Tamoxifen and Raloxifene (STAR) trial and to describe the role that the recruitment process played in the implementation and understanding of breast cancer risk assessment in minority communities. Methods: The NSABP STAR trial was a randomized, double-blinded study comparing the use of tamoxifen 20 mg/day to raloxifene 60 mg/day, for a 5-year period, to reduce the risk of developing invasive breast cancer. Eligible postmenopausal women were required to have a 5-year predicted breast cancer risk of 1.66% based on the modified Gail Model. For the current report, eligibility and enrollment data were tabulated by race/ethnicity for women who submitted STAR risk assessment forms (RAFs). Results: A total of 184, 460 RAFs were received, 145, 550 (78.9%) from white women and 38, 910 (21.1%) from minority women. Of the latter group, 21, 444 (11.6%) were from African Americans/blacks, 7913 (4.5%) from Hispanics/Latinas, and 9553 (5.2%) from other racial or ethnic groups. The percentages of risk-eligible women among African Americans, Hispanics/Latinas, others, and whites were 14.2%, 23.3%, 13.7%, and 57.4%, respectively. Programs targeting minority enrollment submitted large numbers of RAFs, but the eligibility rates of the women referred from those groups tended to be lower than the rates among women referred outside of those programs. The average number of completed risk assessments increased among minority women over the course of the recruitment period compared to those from whites. Limitations: We have not addressed all identified barriers to the recruitment of minorities in clinical research. Our risk assessments and recruitment results do not reflect the modified Gail Model for African Americans. Conclusions: Recruitment strategies used in STAR for racial and ethnic minorities contributed to doubling the minority enrollment compared to that in the BCPT and increased the awareness of breast cancer risk assessment in minority communities. Incorporation of new information into models to improve the risk estimation of diverse populations should prove beneficial.